2009
DOI: 10.1261/rna.1600609
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the chloroplast adenosine-to-inosine tRNA editing enzyme

Abstract: Plastids (chloroplasts) of higher plants exhibit two types of conversional RNA editing: cytidine-to-uridine editing in mRNAs and adenosine-to-inosine editing in at least one plastid genome-encoded tRNA, the tRNA-Arg(ACG). The enzymes catalyzing RNA editing reactions in plastids are unknown. Here we report the identification of the A-to-I tRNA editing enzyme from chloroplasts of the model plant Arabidopsis thaliana. The protein (AtTadA) has an unusual structure in that it harbors a large N-terminal domain of >1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
59
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 38 publications
(47 reference statements)
1
59
0
Order By: Relevance
“…In previous reports, we described a genome-wide search for candidate RNA-editing deaminases in the model plant Arabidopsis (Karcher and Bock, 2009;Zhou et al, 2013). The search employed the Patmatch tool (http://www.…”
Section: Identification Of Putative Adenosine Deaminases In the Arabimentioning
confidence: 99%
See 2 more Smart Citations
“…In previous reports, we described a genome-wide search for candidate RNA-editing deaminases in the model plant Arabidopsis (Karcher and Bock, 2009;Zhou et al, 2013). The search employed the Patmatch tool (http://www.…”
Section: Identification Of Putative Adenosine Deaminases In the Arabimentioning
confidence: 99%
“…The specific adenosine deaminase conducting this conversion (termed tadA, for tRNAspecific adenosine deaminase) is an essential enzyme, and inactivation of the tadA gene is lethal, presumably because of the requirement for inosine in the wobble position to read the three Arg codons CGU, CGC, and CGA. A tadA homolog exists in chloroplasts (plastids) of plants and generates inosine-34 in the same tRNA species, tRNA-Arg(ACG) (Delannoy et al, 2009;Karcher and Bock, 2009). Interestingly, the gene encoding the plant tadA homolog (TADA) is not essential, even though plastid protein biosynthesis (Ahlert et al, 2003;Rogalski et al, 2006Rogalski et al, , 2008bFleischmann et al, 2011) and most plastid tRNA species (Rogalski et al, 2008a;Alkatib et al, 2012aAlkatib et al, , 2012b) are known to be essential for cell survival.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These are encoded by the loci At5g28050, At1g68720, At3g05300, At1g48175, and At4g20960 (in order of decreasing similarity). Some of these could be excluded as GDA candidate loci because they were already functionally characterized: The locus At4g20960 was previously shown to code for a deaminase involved in riboflavin biosynthesis (Fischer et al, 2004), and At1g68720 codes for the chloroplastic tRNA adenosine deaminase Arg (Delannoy et al, 2009;Karcher and Bock, 2009). The locus At1g48175 encodes an uncharacterized protein that is highly conserved in plants.…”
Section: Identification Of Gsda From a Thalianamentioning
confidence: 99%
“…Inosine has not been described in mitochondria, but a recent report showed that a bacteria-type ADATa enzyme plays key functions in inosine formation and thus translation in chloroplasts (16,17). ADATa only targets a single tRNA (tRNA ACG Arg ) and can efficiently catalyze deamination of an anticodon stem loop corresponding to a minimal version of tRNA ACG Arg (4).…”
mentioning
confidence: 99%